Pembentukan Lembaga Baitul Maal Desa (LEBAD) di Desa Curah Cottok, Kecamatan Kapongan, Situbondo - hutama, pandu; Ardyani, Rifqi; Fathur , Muhammad; Intan, Reny; Dwi, Virgalita; Eolia, Exsanti; Al-Faruqi, Muhammad; Yusroni, Akhsin; melinda, Arum; Rofiqoh, Azizah; Winarto, Fariz; Ikmala, Poppy; Hayden, Armando (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2024)
The Baitul Maal Desa Institute (LEBAD) is a social institution engaged in the religious, social and educational fields. This institution was formed as a forum for the distribution and management of zakat, infaq and alms from the community, social funds for BUMDes funds, the government and other parties that are not binding on the Curah Cottok’s empowerment local community who are entitled to receive zakat, infaq and alms. The objectives of establishing LEBAD include reducing the level of poverty, reducing the level of social inequality, and increasing people's welfare. The process of forming a LEBAD consists of several stages, namely village meeting activities, LEBAD management meetings, drawing up of LEBAD notary deed.